2016
DOI: 10.1017/cem.2016.328
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits after Diagnosed Chronic Obstructive Pulmonary Disease in Aboriginal People in Alberta, Canada

Abstract: Objectives: This retrospective cohort study compared rates of emergency department (ED) visits after a diagnosis of chronic obstructive pulmonary disease (COPD) in the three Aboriginal groups (Registered First Nations, Métis and Inuit) relative to a non-Aboriginal cohort. Methods: We linked eight years of administrative health data from Alberta and calculated age-and sex-standardized ED visit rates in cohorts of Aboriginal and non-Aboriginal individuals diagnosed with COPD. Rate ratios (RR) with 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…In Canada, respiratory health inequalities across socioeconomic groups have been identified for a variety of respiratory outcomes in adult populations, including smoking [10] and chronic obstructive pulmonary disease [11][12][13]. Inequalities in paediatric respiratory health have been described for asthma hospitalizations across the urban/rural divide [14], asthma emergency department visits across (large) health zones in Alberta [15], respiratory infections among First Nations and Inuit children [16], and differences in influenza hospitalizations between First Nations populations living on and off reserves [17].…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, respiratory health inequalities across socioeconomic groups have been identified for a variety of respiratory outcomes in adult populations, including smoking [10] and chronic obstructive pulmonary disease [11][12][13]. Inequalities in paediatric respiratory health have been described for asthma hospitalizations across the urban/rural divide [14], asthma emergency department visits across (large) health zones in Alberta [15], respiratory infections among First Nations and Inuit children [16], and differences in influenza hospitalizations between First Nations populations living on and off reserves [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, COPD is the most common cause of chronic disease hospitalization in Canada 7. Studies suggest that the Aboriginal population of Canada has a higher incidence of COPD and a greater burden of disease compared to the non-Aboriginal Canadian population 8,9. These differences are likely due to disparities in smoking, demographic, socioeconomic and environmental risk factors between the Aboriginal and non-Aboriginal population of Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles reported higher visit rates for LRTI [ 98 , 99 ]. Ospina’s article showed increased visit rates for all Indigenous communities except for Métis people for whom no difference was reported [ 92 ]. In articles discussing multiple acute health conditions, 2 articles found higher visit rates [ 31 , 40 ] while 4 articles reported no difference [ 26 , 27 , 43 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…For Indigenous patients with pneumonia or COPD, three studies revealed an increased length of hospital stay [ 55 , 56 , 114 ], two studies found no difference [ 54 , 115 ] and five studies showed decreased length of stay when compared to non-Indigenous patients [ 22 , 49 , 50 , 92 , 93 ]. Two articles mentioned longer hospitalisations for burn injuries [ 58 , 116 ].…”
Section: Resultsmentioning
confidence: 99%